P3.282 Multi-Antigen Sequence Types (NG-MAST) and Antimicrobial Susceptibilities on Neisseria Gonorrhoeae Isolated in Canada, 2010–2011. (13th July 2013) - Martin, I; Sawatzky, P; Liu, G; Allen, V; Hoang, L; Lefebvre, B; Lovgren, M; Wong, T
Abstract : Background: Neisseria gonorrhoeae have acquired resistance to many antibiotics and have developed decreasing susceptibilities to 3rd generation cephalosporins. Method: NG-MAST sequence types and minimum inhibitory concentration (MICs) by agar dilution were determined for each N. gonorrhoeae isolate collected by Canadian provincial public health laboratories and submitted to the National Microbiology Laboratory between 2010–2011 (N = 2391). Isolates are submitted to the NML only when the provincial laboratories identify resistance to at least one antibiotic or if the provincial laboratories do not conduct any antimicrobial susceptibility testing. MIC interpretations were based on the criteria of the Clinical Laboratory Standards Institute (CLSI) and the World Health Organization (WHO) criteria for decreased susceptibility to cephalosporins. Results: Among all the isolates tested in Canada during 2010–2011, 23.5% (1489/6330) were resistant to penicillin, 31.8% (2014/6330) to tetracycline, 28.9% (1828/6330) to erythromycin, 32.4% (2051/6330) to ciprofloxacin and 0.8% (50/6330) to azithromycin. Based on the WHO guidelines for decreased susceptibility to cefixime MIC ≥ 0.25 mg/L and decreased susceptibility to ceftriaxone MIC ≥ 0.125 mg/L, 3.3% (98/2970) of isolates had decreased susceptibility to cefixime in 2010. This number rose to 4.2% (140/3360) in 2011. Ceftriaxone MICs decreased slightly from 7.2% (218/2970) of isolates with decreased susceptibility in 2010 to 6.2% (208/3360) isolates with decreased susceptibility in 2011. In 2010, 249 STs were identified: the most common STs were ST1407, ST3150 and ST3158 at 13.3%, 11.3% and 9.0% respectively. In 2011, 238 STs were identified: the most common STs were ST1407, ST3307 and ST3550 at 15.3%, 9.3% and 5.9% respectively. Conclusions: Detecting changing antibiotic susceptibilities of N. gonorrhoeae isolates in Canada has resulted in the modification of treatment guidelines. Canada's most prevalent NG-MAST type, ST1407 is internationally reported and is of particular interest as it is responsible for cefixime and ceftriaxone treatment failures.